Access to hip arthroplasty and rates of complications in different socioeconomic groups: a review of 111, 000 patients in a universal healthcare system. (2nd May 2022) - Atrey, Amit; Pincus, Daniel; Khoshbin, Amir; Haddad, Fares S.; Ward, Sarah; Aktar, Suriya; Ladha, Karim; Ravi, Bheeshma
Abstract : Aims: Total hip arthroplasty (THA) is one of the most successful surgical procedures. The objectives of this study were to define whether there is a correlation between socioeconomic status (SES) and surgical complications after elective primary unilateral THA, and investigate whether access to elective THA differs within SES groups. Methods: We conducted a retrospective, population-based cohort study involving 202 hospitals in Ontario, Canada, over a 17-year period. Patients were divided into income quintiles based on postal codes as a proxy for personal economic status. Multivariable logistic regression models were then used to primarily assess the relationship between SES and surgical complications within one year of index THA. Results: Of 111, 359 patients who underwent elective primary THA, those in the lower SES groups had statistically significantly more comorbidities and statistically significantly more postoperative complications. While there was no increase in readmission rates within 90 days, there was a statistically significant difference in the primary and secondary outcomes including all revisions due (with a subset of deep wound infection and dislocation). Results showed that those in the higher SES groups had proportionally more cases performed than those in lower groups. Compared to the highest SES quintile, the lower groups had 61% of the number of hip arthroplasties performed. Conclusion: Patients in lower socioeconomic groups have more comorbidities, fewer absolute number of cases performed, have their procedures performed in lower-volume centres, and ultimately have higher rates of complications. This lack of access and higher rates of complications is a "double hit" to those in lower SES groups, and indicates that we should be concentrating efforts to improve access to surgeons and hospitals where arthroplasty is routinely performed in high numbers. Even in a universal healthcare system where there are no penalties for complications such as readmission, there seems to be an inequality in the access to THA. Cite this article: Bone Joint J 2022;104-B(5):589–597.